Evaluation of Hesperidin-Zinc Complex as a Novel Therapeutic Agent for Depression Treatment in Rats - Mahato, Ankit Kumar; Y, Jyothi; Gurung, Sushil; Samanta, Sairashmi; Hondale, Maheshkumar (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Introduction: The complex contains hesperidin and zinc. The zinc is essential micronutrient that is important for human metabolism and catalyzes over 100 enzymes. It can be used to treat Wilson disease, decreased immunity, acute and chronic diarrhea. The hesperidin is a bioflavonoid found in many citrus plants. It has numerous activities like antioxidant, antibacterial, antimicrobial, anti-inflammatory, used to treat inflammation, Hypotension, varicose veins, venous ulcer, oxidative stress. There is no scientific evidence to support the claim that the complex of hesperidin and zinc have antidepressant properties even though zinc and hesperidin both separately have been linked to antidepressant activity in the literature. Objectives: The aim of this research is to find out whether complex of hesperidin and zinc can prevent reserpine induced depression. Methods: Wistar rats were used in this study after acclimatization. The induction group will be induced with reserpine to produce the depression in rats. The experiment included various treatment group of high and low dose of the test drug. Rats were used for the assessments, based on behavioral parameter like tail suspension test (TST), forced swimming test (FST), and elevated plus maze test then histopathology of hippocampus, cortical and substantia nigra region has been analysed, and along with measuring the BDNF levels. Results: On reserpine induced depression, complex of Hesperidin and zinc at low dose (100 mg/kg) shows negligible improvement in depressed behavior, when compare with standard fluoxetine (10 mg/kg). On the other hand, high dose (200 mg/kg) of the complex shows greater improvement also showed normal morphology in all 3 regions of the brain and showed increased level of BDNF in brain compared to low dose (100 mg/kg). Conclusions: Hesperidin-zinc complex was discovered to be a successful antidepressant drug, according to the study's findings. According to the findings, however a high dose of complex is more effective at treating reserpine induced depression than a low dose of complex.